IMPLICATURE AND CONTEXT IN MAHER ZAIN'S “LOVE WILL PREVAIL”: A PRAGMATIC STUDY - Maharani Allysyah Putri; Iskandar Iskandar; Ahmad Rizal Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study examines the forms of implicature in the lyrics ofLove Will Prevailby Maher Zain using a pragmatic approach based on HP Grice's theory of implicature. The research aims to identify the types of conventional and conversational implicatures found in the song and to analyze how situational and cultural contexts influence the interpretation of its implied meanings. This study employs a qualitative descriptive method, with the song lyrics serving as the primary data source. Data were analyzed through identification, classification, and interpretation of implicature types, followed by contextual analysis. The findings reveal that both conventional and conversational implicatures are present in the lyrics. However, conversational implicature is more dominant (62.5%) than conventional implicature (37.5%). The flouting of conversational maxims particularly the maxims of quantity, relevance, and manner functions as a strategic rhetorical device to convey emotional depth, collective suffering, hope, and spiritual resilience. Furthermore, the interpretation of implicature is strongly influenced by situational context, such as global humanitarian crises, and cultural-religious values embedded in the lyrics. These contextual dimensions expand the meaning beyond literal interpretation and position the song as a form of moral and humanitarian discourse. The study concludes that song lyrics function not only as artistic expression but also as pragmatic communication rich in implicit meaning. The application of Grice's theory demonstrates its continued relevance in analyzing contemporary musical discourse.